Prevalence of Constipation Symptoms in Fecally Incontinent Nursing Home Residents - Schnelle, John F. (2009)
OBJECTIVES: To determine the prevalence of constipation symptoms and the effects of a brief toileting assistance trial on constipation in a sample of fecally incontinent nursing home (NH) residents. DESIGN: Observational study. SETTING: Five NHs. PARTICIPANTS: One hundred eleven fecally incontinent NH residents. MEASURES: Research staff measured bowel movement frequency every 2 hours for 10 days. The following week, residents were offered toileting assistance every 2 hours for 2 days to determine resident straining, time required for a bowel movement, and resident perceptions of feeling empty after a bowel movement. Constipation data were abstracted from the medical record. RESULTS: The frequency of bowel movements during usual NH care was low (mean = 0.32 per person per day), and most episodes were incontinent. The frequency of bowel movements increased significantly, to 0.82 per person per day, and most episodes were continent during the 2 days that research staff provided toileting assistance. Eleven percent of residents showed evidence of straining, and 21% of the time after a continent bowel movement, residents reported not feeling empty. Five percent of participants had medical record or Minimum Data Set documentation indicative of constipation symptoms. CONCLUSION: Low rates of bowel movements during the day that are potentially indicative of constipation were immediately improved during a 2-day trial of toileting assistance in approximately 68% of the residents, although other symptoms of constipation remained in a subset of residents who increased toileting frequency.